Analysis Of Readiness For Smart City Implementation In Blora City Indonesia - Joko Handoyo; Indra Gunawan; Retno Wahyusari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Smart city is a concept initiated by the forum for the future which is predicted to be able to solve all aspects of problems in the lives of urban communities. The Smart City Framework consists of six aspects, namely Smart Governance, Smart Economy, Smart Branding, Smart Living, Smart Society and Smart Environment. However, this concept is too broad and complex, covers many things and involves many parties who will be involved in its implementation, so it is needed mature concepts and frameworks as a reference in implementation. Apart from that, each city has different problem characteristics, so it is necessary to carry out analytical studies to find out the problems in each aspect of a smart city. This research aims to analyze the readiness for smart city implementation in the city of Blora, Central Java Province, Indonesia. This analysis will be carried out on 6 aspects of smart cities which will be divided into 17 variables. The approach taken is a qualitative method where an assessment of readiness to achieve achievement targets is carried out through interviews. From the analysis that has been carried out, it can be said that the readiness achieved by the City of Blora for Smart City implementation has reached 66.7% so it still really needs to be improved.